LEGAL REFORM DELIK CONTEMPT of COURT DALAM RUU KUHP 2019 - Wirya Darma, I Made (DiH: Jurnal Ilmu Hukum, 2020)
AbstractArticle 281 letter c of the latest draft of the 2019 Criminal Code Draft states that everyone unlawfully records, publishes directly, or permits publication of anything that could affect the impartiality of judges in a court sentenced to a maximum of 1 year in prison. Other actions that fall into the contempt of court category are being disrespectful towards judges or trials or attacking the integrity or impartiality of judges in court hearings. Likewise with the provisions of Article 282 of the 2019 Criminal Code Bill, there are two types of criminal acts that threaten advocates in the article. First, enter into an agreement with the opposing client if he knows or rightly suspects that the act could harm the client's interests. Second, influencing clerks, surrogates, bailiffs, witnesses, interpreters, investigators, public prosecutors, or judges in a case, with or without compensation. Someone can be considered violating if they meet the contempt of court offense, namely; (a) does not comply with court orders or judges' decisions issued for the benefit of the judicial process; (b) being disrespectful towards judges or trials or attacking the integrity or impartiality of judges in court hearings; (c) and illegally record, publish directly, or allow to be published anything that could affect the impartiality of the judge in a court of law. The editorial of the article needs to be clarified, for example related to what is meant by disrespectful actions or attacking the integrity of judges so as not to cause multiple interpretations in its application. So there is the potential for criminalization of those who criticize or broadcast information, thus affecting the independence of judges. There is concern that the contempt of court article or contempt of the court in the Criminal Code Bill has the potential to become a rubber article. The offense contempt of court is already regulated in the Criminal Code, but the concept of the contempt of court in the Criminal Code Bill has a different interpretation which is even more targeted at judicial critics.Keywords: contempt of court; criminal law; legal reform AbstrakPasal 281 huruf c draf terbaru RUU KUHP 2019 menyatakan, setiap orang secara melawan hukum merekam, mempublikasikan secara langsung, atau membolehkan untuk dipublikasikan segala sesuatu yang dapat mempengaruhi sifat tidak memihak hakim dalam sidang pengadilan dipidana penjara paling lama 1 tahun. Tindakan lain yang masuk dalam kategori contempt of court yakni bersikap tidak hormat terhadap hakim atau persidangan atau menyerang integritas atau sifat tidak memihak hakim dalam sidang pengadilan. Demikian juga dengan ketentuan Pasal 282 RUU KUHP 2019, ada dua jenis tindak pidana yang mengancam advokat di pasal tersebut. Pertama, mengadakan kesepakatan dengan pihak lawan klien jika mengetahui atau sepatutnya menduga bahwa perbuatan tersebut dapat merugikan kepentingan kliennya. Kedua, mempengaruhi panitera, panitera pengganti, juru sita, saksi, juru bahasa, penyidik, penuntut umum, atau hakim dalam perkara, dengan atau tanpa imbalan. Seseorang bisa dianggap melanggar bila memenuhi delik contempt of court, yakni; (a) tidak mematuhi perintah pengadilan atau penetapan hakim yang dikeluarkan untuk kepentingan proses peradilan; (b) bersikap tidak hormat terhadap hakim atau persidangan atau menyerang integritas atau sifat tidak memihak hakim dalam sidang pengadilan; (c) dan secara melawan hukum merekam, mempublikasikan secara langsung, atau membolehkan untuk dipublikasikan segala sesuatu yang dapat mempengaruhi sifat tidak memihak hakim dalam sidang pengadilan. Redaksional dari pasal tersebut perlu diperjelas, misalnya terkait dengan apa yang dimaksud tindakan tidak hormat atau menyerang integritas hakim sehingga tidak menimbulkan multitafsir dalam penerapannya. Sehingga ada potensi kriminalisasi terhadap pihak-pihak yang mengkritik atau menyiarkan informasi, sehingga memengaruhi independensi hakim. Muncul kekhawatiran pasal contempt of court atau penghinaan terhadap pengadilan dalam RUU KUHP berpotensi jadi pasal karet. Delik contempt of court memang sudah diatur dalam KUHP, namun konsep contempt of court dalam RUU KUHP memiliki tafsir berbeda yang justru lebih menyasar pengkritik peradilan.Kata kunci: contempt of court; hukum pidana; legal reform